An Adolescent with innumerable myomas - Baral, J; Gurung, G; Mishra, S; Rai, N; Paudyal, P; Shrestha, B; Rana, A (Journal of Institute of Medicine Nepal, 2013)
Myoma is rare in younger age group, so tends to be mistaken for adnexal tumour. A 19 year old adolescent who was taken for laparotomy for ovarian germ cell tumour instead was found to have uterus studded with innumerable myomas, which were surgically removed through tedious yet successful myomectomy of 40 myomas, thus deserving description. DOI: http://dx.doi.org/10.3126/joim.v34i1.9122 Journal of Institute of Medicine, April, 2012; 34:1 40-42